Stabilization programs and policy credibility: Peru in the 1990s - Myriam Quispe-Agnoli (Federal Reserve Bank of Atlanta, 2003)
This paper uses a rational expectations macroeconomic model in which economic agents formulate the probability about the sustainability of the economic policy—that is, policy credibility—using current and lagged values of government expenditures and lagged values of the inflation rate. The estimation of the model is based on Hamilton's switching regime procedure. The contribution of this paper is the empirical estimation of the credibility of the stabilization program implemented in Peru in August 1990. The results of the estimation show that there are two different regimes in the government expenditure process. According to the economic agents' inferences, the stabilization program in Peru is not credible. This lack of credibility in the economic policy of the government authority explains the presence of hysteresis in currency substitution between August 1990 and June 1995. The estimation involves an expected inflation rate that includes the credibility of the economic policy in its formulation.
Keywords: 330